Improving dental emergency literacy for preschool teachers and parents - Nelwan, Sindy Cornelia; Puteri, Mega Moeharyono; Wicaksono, Dimas Prasetianto; Leo, Leviena Merlynike; Kumalasari, Agnes Herlina; Prayogo, Rosiana Dewi; Nisak, Rosyida Ainun; Karuniadewi, Anak Agung Sagung Dyah; Putri, Sofia Tandya; Ardani, Pradhika; Nasia, Avina Anin (Community Empowerment, 2025)
Medical emergencies can occur in dentistry, including trauma to primary teeth. The global prevalence of dental trauma in children is 10-15%. Trauma to primary teeth can have severe medical, aesthetic, and psychological impacts. Parents and teachers at school are among the most important actors in providing emergency dental care for children. Therefore, providing information that increases parents’ and teachers’ knowledge about pediatric dental emergencies must be done so that appropriate management can be carried out. The method used was training on managing pediatric dental emergencies for parents and teachers at Whiz Kids Playschool Kindergarten. The evaluation showed increased participants’ knowledge before (Range = 10–80, Mean = 47.2) and after (Range = 70–100, Mean = 87.0) the training. Thus, this training successfully increased parents’ and teachers’ knowledge of managing pediatric dental emergencies.